PENGARUH KEMIRINGAN DAN ARAH HADAPAN PEMASANGAN PHOTOVOLTAIC PENERANGAN JALAN UMUM (PJU) DI UNIVERSITAS TADULAKO TERHADAP DAYA OUTPUT - M. Arham; Baso Mukhlis; Nurhani Amin; Agustinus Kali; Muh. Aristo Indrajaya (Foristek, 2022)
Utilization of solar energy in the generation of electrical energy has been widely carried out using solar panels. One example of its use at Tadulako University is public street lighting using solar energy as a source of electricity. The solar panels that have been installed so far have not been effective because of the different tilt angle positions. There are those who can capture the maximum rays of the sun and there are those who cannot capture the maximum rays of the sun and consequently the electrical energy generated is not optimal.The purpose of this study was to determine the effect of changes in orientation and angle of inclination of solar panels on the output power and to optimize the performance of PLTS-based public street lighting in Tadulako University. The method used to determine the effect of the photovoltaic slope on the output power is to measure the short-circuit voltage and current from various forward directions and tilt angles.The influence of the slope and the direction of the front of the photovoltaic installation can be seen that the highest output voltage is 18.82V in the forward-to-west position with an angle of 5˚. The highest short-circuit current is 3.82A in the front-to-west position with a slope angle of 5˚. The highest output power is 47.97W in the front-to-west position with a slope angle of 5˚.